Efforts to Improve Prayer Worship Skills through Demonstration Methods for Students at SD Negeri 100560 Nahula - Dongoran, Nurdin Efendi (MANDAILING GLOBAL EDUKASIA, 2024)
This study was conducted with the background of the level of students' prayer worship skills through the demonstration method in grade III students at SD Negeri 100560 Nahula, Dolok Sigompulon District, North Padang Lawas Regency, which is still below the Minimum Completion Criteria (KKM) of 70 (seventy). This study aims to determine whether the demonstration method can improve students' prayer worship skills. This study used the Classroom Action Research method with respondents of grade III (three) students of SD Negeri 100560 Nahula, Dolok Sigompulon District, North Padang Lawas Regency, totaling 32 students. This study began in January to June 2022. The results of the study showed that the demonstration method on the material on the practice of obligatory prayers succeeded in improving students' prayer worship skills. It can be said that by using the demonstration method in Islamic Religious Education lessons, prayer skills include prayer movements, prayer readings and a combination of both properly and correctly, and are able to increase students' activeness, enthusiasm and desire to like prayer worship lessons more. This can be seen from the results of the analysis of the achievement of learning outcomes in the practice of prayer worship skills, the initial ability before the action was 67.7, then after the action was carried out in two cycles, there was an increase in cycle I of 72.3 and in cycle II the average achievement of the assessment was 76 with a percentage of completion of 100%. From the results of the study and discussion, it can be concluded that by using the demonstration method on the subject of prayer movement practice, students' prayer worship skills can be improved. In addition, students are able to improve movements, prayer readings that are considered still less than perfect, and it is easier to understand and remember lessons through direct practice, rather than just theory. The suggestion that can be submitted is that to instill the concept of prayer movement practice, teachers can use the demonstration method